Correlation between Dental Hygiene Student's Gender Sensitivity and Gender Role Stereotypes - Ji-Min Hwang; Ji-Hyoung Han (The Korean Society of Dental Hygiene Science, 2021)
Background: The purpose of this study is to identify the gender sensitivity and gender role stereotypes of students in dental hygiene and to provide basic data to expand social awareness of equal gender sensitivity and gender role in dental hygiene and students by identifying the degree of correlation.Methods: The purpose of this study was to study dental hygiene students at colleges in Gyeonggi and Chungcheong areas. The survey was conducted from April 1 to April 30, 2021. The final sample was analyzed on 157 subjects. T-test and ANOVA analysis were performed to compare gender sensitivity and gender role stereotypes according to general characteristics. Equal variances were tested using the Levene statistic, and significant differences between groups were identified through Scheffe's post hoc analysis. Pearson's correlation analysis was performed to confirm the correlation between gender sensitivity and gender role stereotypes.Results: Gender sensitivity was 2.69 and gender role stereotypes were 1.83. Among the sub-areas of gender sensitivity, gender role openness was the highest at 2.86, and non-violence was the lowest at 2.50. As for gender role stereotypes, social stereotypes were the highest among sub-areas at 1.71. Among the general characteristics, there was a statistically significant difference in gender sensitivity according to the presence or absence of opposite sex friends (p=0.011). The gender identity openness of gender sensitivity and the physical sub-areas of gender role stereotypes showed the highest positive correlation(r=0.955). Among the sub-areas of gender sensitivity, gender role openness and domestic stereotypes showed the lowest negative correlation (r=−0.404) among the sub-areas of gender role stereotypes.Conclusion: Dental hygiene students should be able to critically analyze and solve problems of not only sexual violence but also gender discrimination and imbalance in social life. For this, environmental factors such as school education and professor guidance must be strengthened.